Quantitative MR neurography biomarkers in 5q-linked spinal muscular atrophy. (13th August 2019) - Kollmer, Jennifer; Hilgenfeld, Tim; Ziegler, Andreas; Saffari, Afshin; Sam, Georges; Hayes, John M.; Pietsch, Adriana; Jost, Marie; Heiland, Sabine; Bendszus, Martin; Wick, Wolfgang; Weiler, Markus
Abstract : Objective: To characterize and quantify peripheral nerve lesions and muscle degeneration in clinically, genetically, and electrophysiologically well-classified, nonpediatric patients with 5q-linked spinal muscular atrophy (SMA) by high-resolution magnetic resonance neurography (MRN). Methods: Thirty-one adult patients with genetically confirmed 5q-linked SMA types II, IIIa, and IIIb and 31 age- and sex-matched healthy volunteers were prospectively investigated. All patients received neurologic, physiotherapeutic, and electrophysiologic assessments. MRN at 3.0T with anatomic coverage from the lumbosacral plexus and proximal thigh down to the tibiotalar joint was performed with dual-echo 2D relaxometry sequences with spectral fat saturation and a 3D T2-weighted inversion recovery sequence. Detailed quantification of nerve injury by morphometric and microstructural MRN markers and qualitative classification of fatty muscle degeneration were conducted. Results: Established clinical scores and compound muscle action potentials discriminated well between the 3 SMA types. MRN revealed that peroneal and tibial nerve cross-sectional area (CSA) at the thigh and lower leg level as well as spinal nerve CSA were markedly decreased throughout all 3 groups, indicating severe generalized peripheral nerve atrophy. While peroneal and tibial nerve T2 relaxation time was distinctly increased at all analyzed anatomic regions, the proton spin density was clearly decreased. Marked differences in fatty muscle degeneration were found between the 3 groups and for all analyzed compartments. Conclusions: MRN detects and quantifies peripheral nerve involvement in SMA types II, IIIa, and IIIb with high sensitivity in vivo. Quantitative MRN parameters (T2 relaxation time, proton spin density, CSA) might serve as novel imaging biomarkers in SMA to indicate early microstructural nerve tissue changes in response to treatment.